Influence of ionophore addition to high-grain diets on net nutrient absorption - D.L. Harmon; T.B. Avery (Kansas Agricultural Experiment Station Research Reports, 1986)
Adding ionophores to a high grain diet increased glucose absorption and decreased the transport of urea back into the gut. These changes are consistent with the antibiotic effects of these compounds. Decreased microbial activity in the gut and shifts in the pattern of absorbed nutrients may help explain the improvements in feed efficiency seen with ionophore addition.
Keywords: Cattlemen' s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Ionophore; Diet; Microbes